Impact of temperature on chlorine contamination and segregation for Ti(C, N) CVD thin hard coating studied by nano-SIMS and atom probe tomography. (1st February 2022) - Azhari, Idriss El; Barrirero, Jenifer; Valle, Nathalie; García, José; von Fieandt, Linus; Engstler, Michael; Soldera, Flavio; Llanes, Luis; Mücklich, Frank
Abstract: High resolution characterization by Atom Probe Tomography (APT) and Secondary Ion Mass Spectrometry (SIMS) imaging were combined to highlight the nature of chlorine contamination and impact of deposition temperature for chemical vapor deposited Ti(C, N) thin hard coating. It is highlighted that chlorine is spread and segregates exclusively at the grain boundaries. With increasing temperature (at 930°C), columnar grains of Ti(C, N) become coarser and chlorine segregation at the grain boundaries is reduced about 3 times in comparison to lower temperature (at 885°C). It also appears that chlorine is less homogeneously distributed with chlorine rich/free regions as it is demonstrated by the powerful combination of nano-SIMS and APT which gave a great insight of the spatial distribution of segregating elements at grain boundaries at nano- and micrometric scales. Graphical abstract: Image, graphical abstract